Post-Disaster Rehabilitation And Reconstruction Policy Study: Between Public Interest And Project Politics - Wilda Sumarsyah (Journal of Politica Governo, 2025)
As an archipelagic nation, Indonesia is highly vulnerable to natural disasters, both geological and hydrometeorological, making the need for post-disaster policies particularly urgent. Post-disaster rehabilitation and reconstruction go beyond rebuilding physical infrastructure; they also encompass social, economic, and psychological recovery, as well as aspects of sustainable development. However, in practice, post-disaster policies are often mired in project-based political interests, with funding allocation, aid distribution, and prioritization of recovery areas influenced by electoral agendas and political patronage. This shifts policy orientation from meeting the needs of survivors to elite legitimacy, potentially leading to unfair distribution of benefits and marginalization of vulnerable groups. Furthermore, private sector involvement in the reconstruction process is often tainted by short-term economic interests that neglect the humanitarian dimension. Bureaucratic fragmentation, overlapping authority, and weak coordination mechanisms further undermine the effectiveness of recovery policies. These conditions demonstrate that post-disaster policies are not a neutral space, but rather a political arena rife with competing interests. Therefore, principles of good governance such as transparency, accountability, public participation, and independent oversight must be foundational to implementation. This research uses a qualitative approach with a literature review method to examine the dynamics of project politics and public interest in post-disaster policies. The literature analysis allows for the identification of patterns of policy distortion as well as opportunities for governance reform. Thus, this study seeks to provide theoretical and practical contributions to formulating more equitable, inclusive, and sustainable post-disaster policies.